2019
DOI: 10.1002/aur.2085
|View full text |Cite
|
Sign up to set email alerts
|

Social and delay discounting in autism spectrum disorder

Abstract: Current literature is divided over whether and how processes such as perspective taking and reward sensitivity differ between individuals with autism spectrum disorder (ASD) versus neurotypical individuals. Discounting tasks may provide novel insight into how these processes operate. In delay discounting tasks, participants choose between smaller immediate rewards and larger delayed rewards, and in social discounting tasks, participants choose between a smaller monetary rewards for themselves versus a larger r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 50 publications
2
15
1
Order By: Relevance
“…Our findings support the results from two previous studies showing that autistic participants are less influenced by social distance manipulations (Tei et al, 2019;Warnell et al, 2019). Our data support Tei et al's (2019) findings showing increased generosity to socially distant others in autism but are not consistent with Warnell et al's (2019) findings who found reduced generosity to closer others in autism. As in Tei et al (2019), we only investigated adults and had six social distances including a stranger condition.…”
Section: Greater Generosity To Socially Distant Others In Autismsupporting
confidence: 67%
See 3 more Smart Citations
“…Our findings support the results from two previous studies showing that autistic participants are less influenced by social distance manipulations (Tei et al, 2019;Warnell et al, 2019). Our data support Tei et al's (2019) findings showing increased generosity to socially distant others in autism but are not consistent with Warnell et al's (2019) findings who found reduced generosity to closer others in autism. As in Tei et al (2019), we only investigated adults and had six social distances including a stranger condition.…”
Section: Greater Generosity To Socially Distant Others In Autismsupporting
confidence: 67%
“…To date, two studies have investigated social discounting in autism and have reported divergent results. Warnell et al (2019) found reduced generosity towards closer others in autistic adolescents and young adults compared to a matched non-autistic group, but no differences in generosity toward more socially distant people. In a different study, Tei et al (2019) reported greater generosity to more socially distant others in autistic adults: autistic participants made more consistent prosocial decisions regardless of the closeness of the potential recipient.…”
Section: Social Discounting In Autismmentioning
confidence: 63%
See 2 more Smart Citations
“…Research into discounting in ASC is mixed. Some studies suggest that TD follows the same pattern as in NT individuals (Antrop et al, 2006 ; Demurie et al, 2012 ; Warnell et al, 2019 ), whereas others have found that autistic individuals discount future rewards more steeply than NT controls (i.e., are more impatient; Carlisi et al, 2017 ; Chantiluke et al, 2014 ). To account for individual differences in contagion, the value preferences of the other agents in this study vary in line with the participant’s own preferences.…”
mentioning
confidence: 99%